PERAN RUMAH PINTAR UNIVERSITAS BRAWIJAYA DALAM MEWUJUDKAN GERAKAN LITERASI INFORMASI DI KOTA MALANG - Pratiwi, Kurniasih Yuni; ., Suprihatin (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
Universitas Brawijaya Library has one of the leading work programs in the development and cooperation section, namely managing Smart Homes, because not all universities in Indonesia have this facility as an effort to improve education and community service in realizing an in- formation literate society. The research method is a case study by directly participating in every activity in the Universitas Brawijaya smart house. The results of this study are to describe in detail the activities of work programs that have been carried out in the Smart House of Brawijaya University in order to obtain a clear picture of the importance of the existence of the Smart House in Brawijaya University because it plays a very important role in realizing information literacy in Malang City.